Normal Bodies, Normal Prices: Interdisciplinarity in Victorian Life Insurance - Alborn, Timothy (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractVictorian life insurance offices challenged disciplinarity by inviting doctors and statisticians to work together toward a single aim, hence prompting these professions to depart from the territorialism that otherwise motivated them. They facilitated these links among disciplines by diverting the attention of their expert employees from specific pathologies to a common-enough conception of what counted as "normal" or "natural" in a field of knowledge. Nor did they do so in a way that replicated the reformist agendas of eugenics or social hygiene, which carried the perfectionist impulse of most late-Victorian disciplines into the interdisciplinary arena. Instead, they took the normal as they found it, because it was easier to make money that way than to try and convince people to aspire to a norm that did not yet exist. If interdisciplinarity in life insurance altered usual conceptions of what it meant to possess a normal body or to find one's place on a normal curve, it had a similar effect on the late-Victorian concept of a natural or normal price. Unlike classical and neoclassical economists, who identified cases of price disequilibrium (the economic equivalent of the pathological) and sought to remove obstacles that stood in the way of normal prices, Victorian life offices started with a normal price (their standard set of premiums for healthy-enough lives) and exclusively sold their product to customers who were normal enough to pay it.